Sacred Law in the Holy City : The Khedival Challenge to the Ottomans as seen from Jerusalem, 1829-1841 - Rood, Judith Mendelsohn, (The Ottoman Empire and its Heritage ;, 2004)
The Muslim community's political and socio-economic role in Jerusalem under Ottoman administration during the 1830s is analyzed in this volume from a natural law perspective. A bitter political contest between Sultan Mahmud II and Muhammad Ali Pasha resulted in the military occupation of Syria and imposition of a brutal new political and legal regime which crushed the indigenous elites of southern Syria. Through a careful analysis of the archives of the Islamic law court of Jerusalem, the study offers a fresh appraisal of how the Ottoman Empire ruled Jerusalem and considers the Muslim response, elucidating the reasons for the breakdown of their relations with non-Muslim Ottoman subjects and differentiating the Ottoman understanding of law and government from that of their enemies, the Wahhabis.